The Influence of Literacy Ability to The Interest of Reading and Critical Thinking Ability in Indonesia - Hakim, Farrel Ariella (Jurnal Bahasa Asing, 2024)
Literacy must become a culture that is instilled from an early age so as to produce competent people who are able to understand, involve, use, analyze and transform existing information. This can make a person able to recognize and develop self-potential as an effort to improve self-quality so that they are able to compete with the outside world, to be able to improve this literacy ability, individuals must make literacy a culture that is instilled from an early age so as to produce competent people who are able to understand, surround, use, analyze, and transform existing information. This can make a person able to recognize and develop self-potential as an effort to improve self-quality so that they are able to compete, with good literacy skills, it is hoped that the ability to think critically will also increase.